Computers in the Human Interaction Loop - Waibel, Alexander; Stiefelhagen, Rainer (Human-Computer Interaction Series, 2009)
Computers in the Human Interaction Loop (CHIL) explores a new look at human interfaces, where computers become participants among humans interacting with humans, as opposed to a rigid human-machine interaction dialog. To do so, computers must become perceptually aware and learn to provide services proactively and unobtrusively based on an implicit understanding of human needs. The book integrates a wide range of research topics that represent key elements of this vision including audio-visual perceptual components for such environments; the design, implementation and analysis of novel proactive perceptive services supporting humans; the development of software architectures, ontologies and tools necessary for building such environments and services, as well as approaches for the evaluation of such technologies and services. Divided into five parts: Introduction, Perceptual Technologies, Services, Software Infrastructure, and an Outlook Beyond, the book is based on research carried out by the CHIL Consortium (Computers in the Human Interaction Loop). Based on the premise that machines need to understand the human context and human activities better, the focus is on how machines need to recognize, understand, adapt to and learn from human interests, activities, goals and aspirations, rather than humans having to adapt to machines. Those working in areas such as ambient intelligence, perceptual user interfaces, human-centred computing systems, and other areas of pervasive computing will find this a very valuable reference source.